Efeitos da combinação de paracetamol e cafeína sobre a bioenergética mitocondrial em fígado de camundongos - Gonçalves, Débora Farina (2017)
Paracetamol (acetaminophen, N-acetyl-p-aminofenol, APAP) is a drug with analgesic and antipiretic effects, widely used, presenting low cost, easier aquisition and clinical efficacy. Accidental or intentional use of high doses APAP may cause hepatic impairment. Caffeine (1,3,7-trimethylxanthine) is an alkaloid of xanthines group, used as stimulant and found in many beverages and pharmacological preparations. Some drugs include the combination of acetaminophen with caffeine. The present study evaluated the effects of paracetamol and caffeine combination on mitochondrial bioenergetics parameters and oxidative stress in mice liver. For this study it was used male swiss albine mice. The animals were treated with a caffeine dose of 20 mg/kg i.p and 30 minutes after were treated with APAP dose of 250 mg/kg APAP i.p. The animals were sacrificed 4 hours after APAP administration. We evaluated mitochondrial and stress oxidative parameters. APAP treatment halved cellular oxygen consumption, moreover impairment mitochondrial complex activities, furthermore, the treatment with APAP increased by three times the swelling in isolated mitochondria from mice liver. Treatment with APAP also increased lipid peroxidation and reactive species production, in livers of mice. On the other hand, caffeine associated with APAP was able to improve bioenergetics mitochondrial function, moreover prevent lipid peroxidation and decrease oxygen reactive species production in mice liver. The results of this work enable the link between effects of caffeine and APAP combination on mitochondrial bioenergetics and oxidative stress parameters.